Study on Inclusive Design of Fitness Equipment for Rural Elderly People: A Case Study of Zhejiang Rural Areas - Tao, Jinbei (Transactions on Social Science, Education and Humanities Research, 2024)
Up against the aging society, this paper applies the concept of inclusive design to conduct in-depth research on public fitness equipment in rural elderly communities, which aims to provide them with more comfortable community fitness equipment, improve the enthusiasm of the elderly people to exercise, and then enhance their physical fitness. Selecting rural elderly people aged 60-75 who have the ability to take care of themselves in Taishun County, Wencheng County and Cangnan County of Zhejiang Province, this study probes into the special needs of elderly people through questionnaire surveys. The results show that the rural elderly people prefer training on endurance, coordination and flexibility, but not keen on strength training. The shortage of fitness facilities, especially rehabilitation, aerobic and flexibility equipment, has been a major obstacle to keeping fitness. Elderly people emphasize the safety and accessibility of equipment, calling for diversified, comfortable and humanized fitness equipment design. This study puts forward a set of design paths based on the inclusive design of public fitness equipment for rural elderly people, so as to effectively improve the fitness willingness and physical fitness of elderly people.